2016
DOI: 10.1002/pi.5158
|View full text |Cite
|
Sign up to set email alerts
|

Novel polypropyleneβ‐nucleating agent with polyhedral oligomeric silsesquioxane core: synthesis and application

Abstract: Synthesis and nucleation ability of a novel silsesquioxane‐based β‐nucleating agent for isotactic polypropylene (iPP) are presented. A silsesquioxane cage (POSS) was octa‐functionalized with a commercially used nucleating agent, namely N2,N6‐dicyclohexylnaphthalene‐2,6‐dicarboxamide (NU‐100), and used as a carrier with the ability to promote crystallization of β‐phase in polypropylene matrix. Presented results include the synthesis route of the β‐nucleating agent (SF‐B01) and a description of its nucleation ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 65 publications
(83 reference statements)
2
17
0
Order By: Relevance
“…It could also be connected with the filler dispersion and tendency of filler particles to aggregate in composites with the filler contents above 5 wt%. The opposite relation was found by Barczewski et al for iso‐ tactic PP composites which contained silsesquioxane‐based β‐nucleating agent. It was demonstrated that the growth of the content of β‐crystals phase in the PP matrix resulted in the improvement of tensile strength and reduction of elongation at break.…”
Section: Resultsmentioning
confidence: 70%
“…It could also be connected with the filler dispersion and tendency of filler particles to aggregate in composites with the filler contents above 5 wt%. The opposite relation was found by Barczewski et al for iso‐ tactic PP composites which contained silsesquioxane‐based β‐nucleating agent. It was demonstrated that the growth of the content of β‐crystals phase in the PP matrix resulted in the improvement of tensile strength and reduction of elongation at break.…”
Section: Resultsmentioning
confidence: 70%
“…These differences could be explained by the absence of the PP β ‐phase crystals in the case of composites with the S4SQ‐18 resin, as evidenced by the WAXS results (Table ). The S4SQ‐18 particles hinder the formation of β ‐phase crystals of PP which are characterized by lower melting temperatures (150–160°C) than more stable α‐crystals (160–170°C) .…”
Section: Resultsmentioning
confidence: 99%
“…The results of spectroscopic analysis of the product confirmed its structure. 1 Three types of silicone resins have been synthesized with differing in amount of SiH groups (and the length of polysiloxane chains connecting network nodes). In all cases, the reactions were carried out according to an identical procedure, changing only the amount of substrates [51].…”
Section: Synthesis Of Octakis[(3-hydroxypropyl)dimethylsiloxy]octasilmentioning
confidence: 99%
“…Silsesquioxanes are widely used as components for the preparation of such materials [1][2][3][4][5][6][7][8][9][10]. Commonly reactive, functionalized polyhedral oligomeric silsesquioxanes of well-defined, 3D structure, bearing one or more functional groups were applied for this purpose [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%